2013
DOI: 10.1039/c3nr05846h
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface plasmon resonance sensors based on wavelength-tunable spectral dips

Abstract: Localized surface plasmon resonance (LSPR) sensors serve as sensitive analytical tools based on refractive index changes, which can be applied to affinity-based chemical sensing and biosensing. However, to select the monitoring wavelength, monodisperse Au or Ag nanoparticles must be synthesized. Here we developed LSPR sensors that operate at arbitrary wavelengths after preirradiation at the corresponding wavelength. Polydisperse plasmonic Ag nanospheroids or nanorods are photocatalytically deposited on TiO2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 51 publications
(28 reference statements)
5
60
0
Order By: Relevance
“…PICS oxidation of Ag is decelerated by appropriate donors or by protecting the NPs with a self-assembled monolayer (SAM) of an alkanethiol or fluoroalkanethiol. 36 Au–Ag alloy NPs are more stable than pure Ag NPs. 29 Ag NPs can also be used stably by coating them with a semiconductor ( e.g.…”
Section: Details Of Picsmentioning
confidence: 96%
See 1 more Smart Citation
“…PICS oxidation of Ag is decelerated by appropriate donors or by protecting the NPs with a self-assembled monolayer (SAM) of an alkanethiol or fluoroalkanethiol. 36 Au–Ag alloy NPs are more stable than pure Ag NPs. 29 Ag NPs can also be used stably by coating them with a semiconductor ( e.g.…”
Section: Details Of Picsmentioning
confidence: 96%
“…10b). Since the absorption dip redshifts with increasing local refractive index, as does the absorption peak, 36 it allows LSPR sensing.…”
Section: Applications Of Picsmentioning
confidence: 99%
“…2 We found that exposure of metal-semiconductor nanocomposite to light at LSPR wavelength induced PICS, which was realized by electron transfer from photoexcited metal nanoparticles to semiconductor. 9,10 In order to further meet the requirements of practical application, a number of studies have focused on how to improve PICS efficiency and photoresponse window, which depend on the shape and size of metal nanoparticles, the interparticle distance, and the contact area between metal and TiO 2 . However, for disordered metal-TiO 2 nanocomposites in the most studied systems, it is difficult to control above mentioned factors exactly and reproducibly.…”
mentioning
confidence: 99%
“…Compared to the relatively inflexible arrangements required for momentum matching in SPR, LSPR works in a simpler configuration as shown in Figure 14C. The measured signal from LSPR is often based on the shift in the spectral peak due to the changes in the maximum extinction condition [114] following analyte binding.…”
Section: Cytokine Sensors With Various Optical Modes Of Detectionmentioning
confidence: 99%